Styles of Leadership, Fears of Compassion, and Competing to Avoid Inferiority - Basran, Jaskaran; Pires, Claudia; Matos, Marcela; McEwan, Kirsten; Gilbert, Paul (Frontiers in Psychology, 2019)
There is general agreement that styles of leadership evolved from mammalian group living strategies that form social ranks. In both primates and humans, different styles of hierarchical dominant-subordinate and leader-follower behaviour can be observed. These can be described in terms of dimensions of antisocial (relatively self-focused, aggressive and threat based) and prosocial (relatively empathic, caring and supportive) interpersonal styles. The aim of this study was to explore how a set of established self-report questionnaires might relate to these dimensions of antisocial and prosocial leadership styles. Two hundred and nineteen students completed questionnaires assessing ruthless self-advancement, coalition building and dominant leadership styles, as well as hypercompetitiveness, narcissism, striving to avoid inferiority, compassion focused and ego focused goals, fears of compassion, and attachment (in)security. A principal component analyses supported an antisocial leadership style factor which compromised of ruthless self-advancement, narcissism and hypercompetitiveness. This was significantly correlated with fears of compassion, ego focused goals, insecure striving (striving to avoid inferiority), fears of losing out, fears of being overlooked, fears of being rejected, and avoidant relating in close relationships. It was significantly negatively correlated with compassionate goals. Although the results did not suggest a factor solution for a prosocial leadership style, we refer to coalition building leadership style here, which showed the opposite patterns, being significantly negatively correlated with narcissism, hypercompetitiveness, fears of compassion, fears of active rejection, and avoidance in close relationships. It was significantly positively correlated with secure striving, compassionate goals, and social safeness. We also found that fears of compassion for others was a partial mediator on the relationships between insecure striving and antisocial leadership style. Moreover, lower fears of compassion for self emerged as a key mediator on the relationship between non-avoidant attachment, secure non-striving and coalition building leadership style. While the motive to accumulate social power, resources and dominance may be linked to antisocial forms of leadership, the intensity of the drive may also be linked to unaddressed threats and fears of rejection and social closeness. Efforts to promote more ethical, moral and prosocial forms of leadership may falter if such fears are left unaddressed.